Interpretation Trail ”Bird Watching” in Bogor Botanical Garden - Hasibuan, Ratna Sari; Nitibaskara, Tubagus Unu; Mahardika, Rangga (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Bogor Botanical Garden (KRB) was a good habitat for birds. Based on KRB’s data of bird, there was an opportunity for KRB to develop birdwatching tourism. Birdwatching completed by interpretation can increase visitor awareness of the importance of conserving natural resources.The aim of research was to develop birdwatching interpretation trail. The research method were the count point method of Indices Ponctuelsd'Abondance (IPA) and line transect method. The interpretation trail map was developed by overlaying the bird's encounter point with the KRB mapusing Arc Software GIS 10.0. The result of this research were 33 bird species that have potential for birdwatching activity. The designedinterpretation trail were the track of water bird, rare bird, and endemic bird sighting.Keywords: birdwatching, Bogor Botanical Garden, interpertation trail